Unites States: A Declining Hegemon? The Rise of a Multipolar World - Tripathi, Maneesha (IJRDO - Journal of Social Science and Humanities Research, 2016)
The collapse of the Soviet Union and its communist allies in Eastern Europe around 1990 spelled the end of bipolarity- a global structure characterized by the competition between the two nuclear superpowers – the United States and the Union of Soviet Socialist Republics – during the Cold War era. The next century was to be the true “American Century” with the rest of the world moulding itself in the image of the global hegemon. The unipolar world allowed the US to loom largely unchallenged for many years and resulted in a peaceful and stable world order. However, with the recent rise of new powers such as the BRIC countries – Brazil, Russia, India and China– the world is moving towards a multi-polar international system. Global governance has become on the whole more diverse, more democratic, more complex, and more competitive. On current trends, in 2020, the US, China and the EU will each have a little fewer than 20 per cent of global GDP, while India will have almost 10 per cent and Japan about 5 per cent. Militarily, the US may still remain the preponderant power, but its relative political influence will be weaker than today. China plans to use its growing economic strength and diplomatic clout to check American power. Russia has already